Microhistories of Composition - McComiskey, Bruce, 1963- (Book collections on Project MUSE., 2016)
""Microhistory explores dialectical interaction of history and cultural history, enabling historians to examine uncommon sites, objects, and agents of historical significance that are overlooked by social history and restricted to local effects by cultural history, and is ideally suited for the complexities of a discipline like composition"--Provided by publisher"--